Electrochemical Generation of Hydrogen and Methanol using ITO Sheet Decorated with Modified-Titania as Electrode - Tariq Abbas; Muhammad Tahir; Nor Aishah Saidina Amin (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Current issues of global warming and environmental pollution due to extensive use of fossil fuels has been reached to an alarming position. Being CO2 as main byproduct of fossil fuel consumption and water as abundantly available on earth surface has great potential to replace fossil fuels as energy source. Herein, electrocatalytic CO2 reduction with water for methanol and hydrogen gas (H2) production over ITO sheet decorated with modified-Titanium nanorods (TiO2 NR), has been investigated. The performance comparison of electrocatalytic activity of hydrothermally modified-titania with commercial TiO2 microparticles (MP) were further investigated. Electrochemical reactor containing KHCO3 aqueous solution with CO2 as an electrolyte and modified TiO2 nanorods (NR) as working electrodes offer an eco-friendly system to produce clean and sustainable energy system. The typical rates of product, i.e. methanol and H2 generation from the ITO sheet decorated with modified TiO2 NR layer recorded higher than those for the ITO sheet with commercial TiO2 microparticle. At 2.0V applied potential vs Ag/AgCl as reference electrode, the modified TiO2 NR electrocatalyst yielded methanol at a rate of 3.32 µmol.cm−2.L−1 and H2 at a rate of 6 µmol.cm−2.L−1 which was higher than that of commercial TiO2 MP electrocatalyst (methanol = 1.5 µmol.cm−2.L−1 and H2 = 3.7 µmol.cm−2.L−1). The enhancement in product yields of methanol and H2 was mainly due to the notable improvements and modification in texture of TiO2 working electrode interface. Hence, it is concluded that the modified TiO2 NR can be considered as a competent candidate for sustainable energy conversion applications. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).